Kindlin-1 and -2 Have Overlapping Functions in Epithelial Cells: Implications for Phenotype Modification - He, Yinghong (American Society for Investigative Pathology, 2011)
Kindlins are a novel family of intracellular adaptor proteins in integrin-containing focal adhesions. Kindlin-1 and -2 are expressed in the skin, but whether and how they cooperate in adult epithelial cells have remained elusive. We uncovered the overlapping roles of kindlin-1 and -2 in maintaining epithelial integrity and show that the phenotype of kindlin-1-deficient cells can be modulated by regulating kindlin-2 gene expression and vice versa. The experimental evidence is provided by use of human keratinocyte cell lines that express both kindlins, just kindlin-1 or kindlin-2, or none of them. Double deficiency of kindlin-1 and -2 had significant negative effects on focal adhesion formation and actin cytoskeleton organization, cell adhesion, survival, directional migration, and activation of β(1) integrin, whereas deficiency of one kindlin only showed variable perturbation of these functions. Cell motility and formation of cell-cell contacts were particularly affected by lack of kindlin-2. These results predict that kindlin-1 and -2 can functionally compensate for each other, at least in part. The high physiologic and pathologic significance of the compensation was emphasized by the discovery of environmental regulation of kindlin-2 expression. UV-B irradiation induced loss of kindlin-2 in keratinocytes. This first example of environmental regulation of kindlin expression has implications for phenotype modulation in Kindler syndrome, a skin disorder caused by kindlin-1 deficiency.